Literature Use in Engineering and Computer Science Research: An Analysis of Works Cited in Dissertations and Theses. - Janet Fransen (Issues in Science and Technology Librarianship, 2012)
Any engineering librarian will tell you that their researchers' literature needs differ from researchers in other disciplines: Books are used less, and conference papers more, than in humanities disciplines. This study analyzes literature cited in theses and dissertations submitted over a three-year period by students in three departments of the University of Minnesota's College of Science & Engineering. The results show how literature type and age differ between engineering researchers and computer scientists and their counterparts in humanities and social sciences. The results also illustrate how particular disciplines within engineering differ in their use of literature and the level to which they make use of the literature of fields outside of their own. [ABSTRACT FROM AUTHOR]